2018
DOI: 10.1097/ccm.0000000000002799
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Activation Contributes to Mechanical Stretch–Induced Endothelial-Mesenchymal Transition and Pulmonary Fibrosis

Abstract: Mechanical stretch may promote endothelial-mesenchymal transition and pulmonary fibrosis through a NLRP3-dependent pathway. The inhibition of endothelial-mesenchymal transition by NLRP3 inactivation may be a viable therapeutic strategy against pulmonary fibrosis associated with mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 39 publications
2
54
0
Order By: Relevance
“…IPF is a progressive, chronic, and ultimately fatal interstitial lung disease characterized by enhanced extracellular matrix deposition. Although the exact etiology in IPF is unclear, complex, and probably diverse, previous studies have identified EndoMT as one of the important processes for the establishment and progression of the fibrotic changes . In our study, we also found that all control groups showed no abnormalities, while WT‐BLM mice showed significant fibrotic responses in the lung; these were accompanied by decreased endothelial markers VE‐cadherin and CD31 but increased mesenchymal cell marker α‐smooth muscle actin (α‐SMA), indicating EndoMT.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…IPF is a progressive, chronic, and ultimately fatal interstitial lung disease characterized by enhanced extracellular matrix deposition. Although the exact etiology in IPF is unclear, complex, and probably diverse, previous studies have identified EndoMT as one of the important processes for the establishment and progression of the fibrotic changes . In our study, we also found that all control groups showed no abnormalities, while WT‐BLM mice showed significant fibrotic responses in the lung; these were accompanied by decreased endothelial markers VE‐cadherin and CD31 but increased mesenchymal cell marker α‐smooth muscle actin (α‐SMA), indicating EndoMT.…”
Section: Discussionsupporting
confidence: 70%
“…Although the exact etiology in IPF is unclear, complex, and probably diverse, previous studies have identified EndoMT as one of the important processes for the establishment and progression of the fibrotic changes. [20][21][22] In our study, we also found that all control groups showed no abnormalities, while WT-BLM mice showed significant fibrotic responses in the lung; these were accompanied by decreased endothelial markers VE-cadherin and CD31 but increased mesenchymal cell marker α-smooth muscle actin (α-SMA), indicating EndoMT. Recent studies have demonstrated that myofibroblasts are the cells ultimately responsible for the severe organ fibrotic process such as in pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 67%
“…Excessive stretch can also lead to production of ROS which enhances EndMT by oxidative stress, [109,129] and TGF-β upregulation by NLRP3 inflammasome activation. [130] …”
Section: Applications Of Vascular Mechanobiologymentioning
confidence: 99%
“…This link is exemplified in inflammatory lung injury diseases like VILI where mechanical ventilation exerts mechanical stress. Ventilator‐induced cyclic stretch of alveolar macrophages activates the macrophage NLRP3 inflammasome, and also in lung endothelial cells, to produce IL‐1β. Mechanotransduction modulates the macrophage inflammatory response in other systems as well .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mechanosensitive inflammasome activation has been implicated in acute respiratory distress syndrome (ARDS) pathophysiology. In a model of VILI, mechanical stress, induced by mechanical ventilation, activated the NLRP3 inflammasome in macrophages and endothelial cells, contributing to lung damage . Similarly, actin depolymerization induced by the mechanical stimulus of cyclic stretch also enhanced NLRP3 activation in tenocytes and consequently promoted tendinitis progression .…”
Section: Introductionmentioning
confidence: 99%